A population-based retrospective cohort study comparing care for Western Australians with and without Alzheimer's disease in the last year of life - Rosenwax, Lorna; McNamara, B.; Zilkens, Renate (Blackwell Publishing, 2008)
Our study investigated health service use for people in the last year of life, comparing those who died with and without Alzheimer’s disease (AD) documented on the death certificate. Using a population-based retrospective cohort design, and utilizing the Western Australian Data Linkage System for the period 2000–2002 (2.5 years), the study found that 992 people died of either AD alone or AD with at least one other condition recorded on the death certificate. Of those with documented AD, 90.4% were aged 75 or more years, two-thirds were female (68.8%), more than one-half were widowed (59.3%) and the majority lived in a major city (77.0%). Most deceased people had comorbidities recorded on death certificates (90.0%); the majority having either two (34.5%) or three (28.8%) comorbid conditions. Over two-thirds of people aged over 75 years with AD died in a residential aged care facility (RACF, 67.4%), while the greatest proportion of people without AD died in hospital (52.9%). When a comparison was made in the use of hospital and community-based services for decedents aged over 75 years with and without AD, dissimilarities were evident. Less than one-half of people with documented AD received hospital care in the last year of life (46.3%) compared to over 80% of people without AD (80.5%). Likewise, fewer people in the Alzheimer’s group received community care when compared to those without documented AD (10.8% vs. 28.5%). Despite a small group of people with AD (5.4%) who were transferred to an RACF shortly before dying, most people in this group lived and died in an RACF and had their care provided in this setting. Adequate nursing, medical and allied health services, and the provision of appropriate social support, including the use of advance care directives in RACFs, are essential for equitable provision of care to people with AD.